The Use Of Learning Media In Avocado Breeding Training At The West Sumatra Agricultural Training Center - Loli Permata Sari; Wisroni Wisroni (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2022)
Against the backdrop of the successful use of avocado breeding training learning media in the West Sumatran Agricultural Training Center. This study aims to see the description of the use of learning media based on the accuracy of the use of media with learning objectives, the accuracy of the use of media with learning materials, the accuracy of the use of media with the understanding of the participants, the accuracy of the use of media with learning methods, the accuracy of the use of media with facilities and infrastructure/locations in West Sumatra Barat Training Center. This type of research is descriptive quantitative research. The population in this study amounted to 60 people. The collection technique uses a questionnaire. The data analysis technique used the percentage technique. The results of this study indicate that (1) the accuracy of the use of media with learning objectives is obtained at 100% intervals, (2) the accuracy of the use of media with learning materials is obtained at 99% intervals, (3) the accuracy of the use of media with participant understanding is obtained at 99% intervals, (4) the accuracy of the use of media with learning methods is obtained at 99.9% intervals, (5) the accuracy of the use of media with facilities and infrastructure/locations is obtained at 99% intervals in the very high category.Keywords: Use of Learning Media, Education and Training